2022
DOI: 10.1021/acs.orglett.2c03297
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of Indeno[1,2-c]furans via Cobalt-Catalyzed Radical–Polar Crossover [3 + 2] Cycloaddition of o-Alkynylaryl β-Dicarbonyls

Abstract: Fused polycyclic furans are privileged structural scaffolds in materials chemistry, including organic semiconductors. Specifically, indeno[1,2-c]furans are an interesting type of polycyclic furans featuring a fused furan and indenone framework. Unfortunately, limited studies on their photophysical properties have been performed, probably owing to the lack of efficient and straightforward approaches to those compounds. Herein, we have developed a cobalt-catalyzed radical−polar crossover cyclization of the readi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 55 publications
0
2
0
Order By: Relevance
“…Regarding the starting materials, we previously demonstrated that indeno[1,2-c]furans (1) can be readily prepared from o-alkynylaryl-tethered β-dicarbonyls via a cobalt-catalyzed radical−polar crossover strategy with superstoichiometric Nfluorobenzenesulfonimide (NFSI) as the oxidant. 46 Starting from o-alkynylaryl-tethered β-dicarbonyl (4a), constantcurrent electrolysis (I = 3 mA) in the presence of Et 3 N•3HF also generated the target indeno[1,2-c]furan (1a) in 65% yield (Scheme 4 and Scheme S6). Compared with the chemical approach, this electrochemical reaction features a simple operation and is greener and more sustainable, as it obviates the need for transition metals as well as excess oxidants of economic and environmental concern.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Regarding the starting materials, we previously demonstrated that indeno[1,2-c]furans (1) can be readily prepared from o-alkynylaryl-tethered β-dicarbonyls via a cobalt-catalyzed radical−polar crossover strategy with superstoichiometric Nfluorobenzenesulfonimide (NFSI) as the oxidant. 46 Starting from o-alkynylaryl-tethered β-dicarbonyl (4a), constantcurrent electrolysis (I = 3 mA) in the presence of Et 3 N•3HF also generated the target indeno[1,2-c]furan (1a) in 65% yield (Scheme 4 and Scheme S6). Compared with the chemical approach, this electrochemical reaction features a simple operation and is greener and more sustainable, as it obviates the need for transition metals as well as excess oxidants of economic and environmental concern.…”
mentioning
confidence: 99%
“…Regarding the starting materials, we previously demonstrated that indeno­[1,2- c ]­furans ( 1 ) can be readily prepared from o -alkynylaryl-tethered β-dicarbonyls via a cobalt-catalyzed radical–polar crossover strategy with superstoichiometric N -fluorobenzenesulfonimide (NFSI) as the oxidant . Starting from o -alkynylaryl-tethered β-dicarbonyl ( 4a ), constant-current electrolysis ( I = 3 mA) in the presence of Et 3 N·3HF also generated the target indeno­[1,2- c ]­furan ( 1a ) in 65% yield (Scheme and Scheme S6).…”
mentioning
confidence: 99%